Implementasi Program Kampung Keluarga Berencana di Kabupaten Pangkajene dan Kepulauan - Hasriani Hasriani; Rabina Yunus; Hamsinah Hamsinah (Spirit Publik: Jurnal Administrasi Publik, 2021)
This study aims to determine the process of implementing the Kampung KB program. This research will focus on what factors determine the process of implementing the village family planning program. The Kampung KB program is a central government program as a manifestation of the Nawacita development priority agenda for the 2015-2019 period. This research was conducted in Pangkajene and archipelago districts by taking two samples of KB village locations, namely in Bungoro sub-district as a sample for mainland sub-district and North Tupabiring sub-district as a sample for archipelago sub-district. The number of informants in this study were 16 people, with the criteria of informants; The leadership of the BKKBN of South Sulawesi Province, the leadership of the DPPKB of Pangkep Regency, the Family Planning Counselor and the community. This study uses a qualitative research method with a case study approach. Primary data were collected through interviews with informants, while secondary data were obtained from documents relevant to this research. Primary and secondary data were then analyzed using Miles and Hubernan's theory with three steps, namely data condensation, data presentation, and drawing conclusions or verification. The indicators used in this study are indicators of policy implementation according to Merilee S Grindel. The results showed that the aspects of the type of benefits and expected changes were supporting aspects and were considered to have run as expected, so it can be said that the implementation of the Kampung KB Program could be declared successful, while the aspects of the resources used still needed to be addressed because of the budget allocation and support. facilities and infrastructure from the central government, family planning instructors are expected to be more creative and innovative in implementing this program.